Morphological Awareness for Vocabulary Acquisition among EFL seventh grade learners at Delfos Elementary School in the period of 2019-2020. - Villamar Ramírez, César Alberto (2020)
This research is about Morphological Awareness for Vocabulary Acquisition among EFL learners at an elementary school in the city of Guayaquil. This represents a problem for students when writing and expressing themselves orally. The main objective is to inquire about the poor vocabulary use and to identify the possible reasons that may be causing the problem. This research work is situated in Unidad Educativa Delfos, a private educational institution mainly targeted to middle income household. The target group of the study are the 29 students of seventh grade between 11 and 12 years old. It was chosen a quasi-experiment research design with a quantitative approach. The aspects considered for the quantitative analysis where the surveys and the tests after the methodology used with the students. The objective of the tests is to examine the level of effectiveness of morphological awareness for vocabulary acquisition among the students. Some important findings were that the students who received morphological relatedness intervention could achieve a better understanding of word formation. Also, morphological relatedness can be very helpful for vocabulary acquisition because it enables the students to identify word families from the very beginning. Finally, according to the analysis, morphological awareness plays an important role in vocabulary acquisition.